2003
DOI: 10.1111/j.1527-3458.2003.tb00241.x
|View full text |Cite
|
Sign up to set email alerts
|

SL651498, a GABAA Receptor Agonist with Subtype‐Selective Efficacy, as a Potential Treatment for Generalized Anxiety Disorder and Muscle Spasms

Abstract: SL651498 (6-fluoro-9-methyl-2-phenyl-4-(pyrrolidin-1-yl-carbonyl)-2, 9-dihydro-1H-pyrido [3,4-b]indol-1-one) was identified as a drug development candidate from a research program designed to discover subtype-selective GABA A receptor agonists for the treatment of generalized anxiety disorder and muscle spasms. The drug displays high affinity for rat native GABA A receptors containing á 1 (K i = 6.8 nM) and á 2 (K i = 12.3 nM) subunits, and weaker affinity for á 5 -containing GABA A receptors (K i = 117 nM). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 55 publications
2
55
0
1
Order By: Relevance
“…First, it is possible that ocinaplon and benzodiazepines act on different GABA A receptor subtypes such that ocinaplon produces its anxiolytic effects through actions on ␣1-containing complexes, whereas benzodiazepines and perhaps other structural classes of compounds (11,12) produce anxiolytic effects through actions on ␣2-containing (GABA A2 ) receptors. This hypothesis is presently 5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, it is possible that ocinaplon and benzodiazepines act on different GABA A receptor subtypes such that ocinaplon produces its anxiolytic effects through actions on ␣1-containing complexes, whereas benzodiazepines and perhaps other structural classes of compounds (11,12) produce anxiolytic effects through actions on ␣2-containing (GABA A2 ) receptors. This hypothesis is presently 5.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, a combination of high relative potency and high relative efficacy at certain receptor subtypes would seem to more parsimoniously explain its anxioselective properties. Finally, although studies using knock-in mice indicate that GABA A1 receptors contribute to the sedative and anticonvulsant properties of benzodiazepines (36,37), pharmacological studies using a selective GABA A1 antagonist (38,39) indicate that the anticonflict (but not the motor impairing) actions of diazepam (11,40) are mediated via GABA A1 receptors. There are other significant inconsistencies between data obtained in knock-in mice and pharmacological studies using subtype selective pharmacological agents in wild type animals (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the study indicated that SL651498 produced ataxia, muscle weakness or sedation at doses much higher than those producing anxiolytic-like activity. No appearance of tolerance to its anticonvulsant effects or physical dependence was observed in mice [357]. SL651498 elicits anxiolytic-like effects similar to conventional BZs.…”
Section: Sl651498mentioning
confidence: 99%
“…Unlike full agonists, partial agonists of the GABA A receptor, particularly those that are subtype-selective (Low et al, 2000;Mohler et al, 2002;Griebel et al, 2003), may afford concurrently the desired anxiolytic effects of a benzodiazepine while minimizing or eliminating its unwanted side effects, resulting in a superior safety profile for the general and chronic treatment of GAD (Lader, 1994).…”
mentioning
confidence: 99%